PERAMALAN NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA DENGAN MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Ardesfira, Gelbi; Zedha, Hazulil Fitriah; Fazana, Iin; Rahmadhiyanti, Julia; Rahima, Siti; Anwar, Samsul (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The Rupiah exchange rate was immensely influential in maintaining the stability of the country's economy. The weakening of the rupiah exchange rate would have an impact on the national economy. Therefore, a forecast was needed to determine the exchange rate of the Rupiah in the future, especially against the US Dollar (USD). This study aimed to predict the rupiah exchange rate against the USD in 2022 and 2023. The data employed were the rupiah exchange rate data against the USD from January 2001 to December 2021. The forecasting method utilized in this study was the Autoregressive Integrated Moving Average (ARIMA) method. The most suitable ARIMA model in forecasting the Rupiah exchange rate against USD was ARIMA (3,1,1). Forecasting results showed the Rupiah exchange rate weakened more significantly in 2022 and 2023, reaching IDR 14,484.5 and IDR 14,704.7 per USD, respectively, with the highest forecast limit reaching IDR 16,691.6 at the end of 2022 and IDR 17,781.8 at the end of 2023. The government needed preparing special policies in an effort to maintain the stability of the rupiah exchange rate in the future.